YOUR CHILD IS MY CHILD: COMMUNITY EDUCATION IN SEXUAL ABUSE FOR A HIGH RISK AREA - Grobler, Herman; van den Heever, Claudi (Social Work/Maatskaplike Werk, 2010)
Sexual abuse of children is a reality that has been present for centuries (Bandi, 2003:1) and research has indicated that the rate of sexual abuse of children is extremely high (Karson, 2001:4). Most parents find it difficult to discuss the topic of sexual abuse with their adolescents, and even more with their pre-school children. This is understandable, as it might even be difficult for parents to discuss general sexual matters with their children. The complexity of the issue is highlighted by Myers and Milner (2007:2), who refer to sex and sexuality as complicated because of the “different discourses, labels and identities” that influence the way people make sense of sexual matters. They also refer to the lack of discussion of sexual matters, or the ways in which these matters are discussed that can lead to confusion. According to Lively and Lively (1991:74), even parents in affluent families may not always explain the sexual act when their children see them having intercourse. This may confuse the children. Children who are exposed to sexual activities on a daily basis can become vulnerable in terms of sexual abuse, because the context of the sexual behaviour is not explained. The parents also do not necessarily teach the children to protect their own bodies and that sexual activities should be reserved for when they are mature.